Benefits of Nature Contact for Children. (November 2015) - Chawla, Louise
This review examines different ways that contact with nature can contribute to the health and well-being of children. Applying the capabilities approach to human development for a broad definition of well-being, it traces research from the 1970s to the present, following shifting research approaches that investigate different dimensions of health. A compelling body of evidence exists that trees and natural areas are essential elements of healthy communities for children. They need to be integrated at multiple scales, from landscaping around homes, schools, and childcare centers, to linked systems of urban trails, greenways, parks, and "rough ground" for children's creative play.